Problematika Administrasi Dapodik dalam Penguatan Kelembagaan PAUD - Mila Fitria Amanda (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
This study examines the administrative problems in managing the Education Data Sistem (Dapodik) as a key instrument for strengthening the institutional capacity of Early Childhood Education (PAUD) in West Sumatra. Using a literature review approach, data were collected from various sources, including reports from the Ministry of Education, Culture, Research, and Technology (Kemendikbudristek), BAN PAUD and PNF, and previous studies. The findings reveal that although Dapodik reporting in West Sumatra has reached 97.8%, several challenges persist, such as limited internet access, low operator competence, insufficient technical supervision, and a lack of institutional awareness of data accuracy. These issues have led to delays in accreditation, misallocation of operational assistance funds (BOP), and ineffective educational planning. Therefore, innovative solutions such as Dapodik gamification, digital inter-institutional mentoring, and operator certification are recommended to improve data management effectiveness and sustainably strengthen PAUD institutional governance.